2015
DOI: 10.1007/s00005-015-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Inhibition of ATM by Phytochemicals: Awakening and Sleeping the Guardian Angel Naturally

Abstract: Double-stranded breaks (DSBs) are cytotoxic DNA lesions caused by oxygen radicals, ionizing radiation, and radiomimetic chemicals. Increasing understanding of DNA damage signaling has provided an ever-expanding list of modulators reported to orchestrate DNA damage repair and ataxia telangiectasia mutated (ATM) is the master regulator and main transducer of the DSB response. Increasingly, it is being realized that DNA damage response is a synchronized and branched network that functionalizes different molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…As a natural phytoestrogen flavonoid widely distributed in vegetables and fruits [1], apigenin (4′,5,7-trihydroxyflavone) effectively inhibits proliferation in multiple cancer cell types, including colon, lung, breast, prostate, melanoma, and leukemia [27] and DNA damage mechanisms were comprised in lots of studies [8]. Apigenin may also exhibit reduced systemic toxicity compared to other flavonoids [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a natural phytoestrogen flavonoid widely distributed in vegetables and fruits [1], apigenin (4′,5,7-trihydroxyflavone) effectively inhibits proliferation in multiple cancer cell types, including colon, lung, breast, prostate, melanoma, and leukemia [27] and DNA damage mechanisms were comprised in lots of studies [8]. Apigenin may also exhibit reduced systemic toxicity compared to other flavonoids [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, APG was demonstrated to induce reactive oxygen species and p38, which are essential substances in the process of cell death (7,13,14). Furthermore, it was observed that APG induced DNA lesions involving DNA breaks (15), micronuclei, chromosomal aberrations (CAs) and chromatid exchanges (16)(17)(18). APG was further demonstrated to have significant topoisomerase I (Top1) inhibitor activities (19).…”
Section: Introductionmentioning
confidence: 99%
“…The realization of the potent anticancer properties of resveratrol was followed by numerous investigations into the various signaling pathways that it affects, leading to the observed effects [12,13,14,15,16,17]. In recent years, the focus of cancer research has shifted to stem cells, epithelial-to-mesenchymal transition (EMT) and epigenetic regulation, even in the context of lead compounds such as resveratrol that have a natural origin.…”
Section: Introductionmentioning
confidence: 99%